The Indian periodical press and the production of nationalist rhetoric - Kamra, Sukeshi (New York, N.Y. : Palgrave Macmillan, 2011)
"This book makes a case for considering the Indian periodical press as a key forum for the production of nationalist rhetoric. It argues that between the 1870s and 1910, the press was the place in which the notion of 'the public' circulated and where an expansive middle class, and even larger reading audience, was persuaded into believing it had force. Kamra shows that the increasingly antagonistic relationship between the press and colonial regime is where and how a nationalist public sphere first develops"--
Introduction: the periodical press, government culture, and the making of the Indian public, 1870-1910 -- The verbal culture of 1857 and the politics of fear -- Law and the periodical press in the 1870s: a culture of complaint -- Criminalizing political conversation: the 1891 trial of the Bangavasi -- The "Infernal Machine" of propaganda literature: the Indian press of 1907-1910 -- Criminalizing political conversation: the trial of the Pallichitra (1910) -- Conclusion: of the Indian press and the colonial government.
Includes bibliographical references.
Keywords: PRESS AND POLITICS -- INDIA -- HISTORY -- 19th CENTURY; PRESS AND POLITICS -- INDIA -- HISTORY -- 20th CENTURY; NATIONALISM IN THE PRESS -- INDIA -- HISTORY -- 19th CENTURY; NATIONALISM IN THE PRESS -- INDIA -- HISTORY -- 20th CENTURY